EMERGING GAMBLING MARKET OF GEORGIA (ECONOMIC DIMENSION) - Besik Bolkvadze (Соціальна економіка)
There are many different views on gambling in the history of mankind, which leads to constant debate about the advantages and disadvantages of gambling. In particular, one group of people sees it as a way to have fun and rejuvenate; the second group considers it as a category of moral decline of human beings; the third group views it as social evil and crime-prone behavior; another group deems gambling as a business activity and supports its legalization. Gambling has negative as well as some positive impact on the economy of the country and the society general. The paper considers the challenging issues of the gambling policy of Georgia in recent years from pragmatic as well as conceptual point of view, where the social losses and economic benefits of gambling are presented.